Practitioner opinions of crisis plans within early intervention in psychosis services: A mixed methods study. (4th March 2021) - Lonsdale, Nikki; Webber, Martin
Abstract: The efficacy of crisis planning in mental health services is contested. As recovery and self‐management are core to Early Intervention in Psychosis (EIP) services and the Care Programme Approach (CPA), the views of EIP practitioners of the most useful aspects of crisis planning can inform this vital aspect of practice. We conducted a mixed methods study using a national cross‐sectional survey ( n = 70) and semi‐structured interviews ( n = 12) with EIP practitioners in England in 2019. Data were analysed using non‐parametric tests and thematic analysis. A Joint Crisis Plan (JCP) template was used as a benchmark to judge current practice by (Sutherby et al., 1999; Henderson et al., 2004; Thornicroft et al., 2013). The most useful crisis plan themes identified by practitioners included early warning signs, triggers and helpful treatments, although not all elements were considered useful. Additionally, the interviews identified that collaboration with clients, carers and other services; personalisation; and self‐management were all considered important in effective crisis planning. The practitioners also identified barriers to effective crisis planning, such as the electronic records system, lack of time and lack of available service provision. The research highlighted the important aspects of EIP and was significant in impacting the service and wider EIP network further. While crisis planning is a significant part of EIP, it does not appear to be consistently applied in practice. Fully implementing collaborative crisis planning in EIP services may require changes to policy, practice and local systems to ensure that crisis planning is as effective as possible.